2019
DOI: 10.1002/cctc.201900919
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous‐Phase Selective Oxidation of Methane with Oxygen over Iron Salts and Pd/C in the Presence of Hydrogen

Abstract: Direct conversion of methane into value‐added chemicals is a challenging but worthwhile subject. In this communication, the direct conversion of methane into methane oxygenates was achieved in an aqueous solution at room temperature using iron salts and Pd/C as catalysts and hydrogen peroxide as an oxidant. The hydrogen peroxide can be directly added or generated in situ from hydrogen and oxygen. The Pd/C catalyst greatly enhanced the reaction rate together with the iron salts. The effect of some parameters su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…% Pd/AC under the same reaction conditions as those employed for the heterogeneous catalyst. Similar to the previous results [35], the total product yield increased but the selectivity to the methane oxygenates decreased with increasing concentration of FeSO4 (Table S10). Figure 3 shows that the total product yield was proportional to the amount of homogeneous Fe species in the reaction system.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…% Pd/AC under the same reaction conditions as those employed for the heterogeneous catalyst. Similar to the previous results [35], the total product yield increased but the selectivity to the methane oxygenates decreased with increasing concentration of FeSO4 (Table S10). Figure 3 shows that the total product yield was proportional to the amount of homogeneous Fe species in the reaction system.…”
Section: Discussionsupporting
confidence: 88%
“…Generally, a better catalytic activity implies worse catalyst stability ( Table 1 and Table S2). Further study with Fe-ZSM-5 confirmed that the effect of some reaction variables such as reaction temperature, pH, and amount of catalyst was similar to that observed when the homogeneous Fe catalyst was used, as reported previously [35]. The ICP analysis of the liquid after the heterogeneous reaction conducted under different conditions supported the observation that the catalytic activity is closely related to the amount of leached Fe species.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations